2016
DOI: 10.7863/ultra.15.11038
|View full text |Cite
|
Sign up to set email alerts
|

Role of Strain Elastography in the Evaluation of Testicular Torsion

Abstract: Our results show that real-time strain elastography can be a complementary method in the evaluation of testicular tissue in testicular torsion and can guide surgeons in their surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…SWE is a newer elastic imaging technology which is a newer variant of RTE [40]. Different from earlier technology, it uses shearwave and does not need to compress and decompress the tissues to generate strain [41]. The shear waves are generated using acoustic radiation force automatically induced by the supersonic speed.…”
Section: Discussionmentioning
confidence: 99%
“…SWE is a newer elastic imaging technology which is a newer variant of RTE [40]. Different from earlier technology, it uses shearwave and does not need to compress and decompress the tissues to generate strain [41]. The shear waves are generated using acoustic radiation force automatically induced by the supersonic speed.…”
Section: Discussionmentioning
confidence: 99%
“…However, US has a role in differentiating delayed presentation of testicular torsion from other pathologies. By comparing the pathological evaluation of the surgical specimen with pre-operative testicular torsion at different time points and different degrees of torsion, Herek et al [30] showed that testicular tissue stiffness gradually increased from 360° to 720° of torsion and became softer at 1,080°, where necrosis occurred and damage to the testes became irreversible. They also showed that the contralateral testis was also affected and presented increased tissue stiffness.…”
Section: Testicular Non-neoplastic Lesionsmentioning
confidence: 99%
“…Elastography is used in various organs 7 9 10 11 and also in the testicles for investigating testicular torsion 12 13 , testicular cancer 14 15 infarction 16 17 , epidermoid cysts 18 , undescended testes 19 , infertile men 20 , hemodialysis patients 21 , testicular microlithiasis, and other lesions 22 23 24 . It can be challenging to distinguish hard tumors in soft tissue using only B-mode ultrasound.…”
Section: Introductionmentioning
confidence: 99%